2023
DOI: 10.3390/rs15092288
|View full text |Cite
|
Sign up to set email alerts
|

Shifted Global Vegetation Phenology in Response to Climate Changes and Its Feedback on Vegetation Carbon Uptake

Abstract: Green vegetation plays a vital role in energy flows and matter cycles in terrestrial ecosystems, and vegetation phenology may not only be influenced by, but also impose active feedback on, climate changes. The phenological events of vegetation such as the start of season (SOS), end of season (EOS), and length of season (LOS) can respond to climate changes and affect gross primary productivity (GPP). Here, we coupled satellite remote sensing imagery with FLUXNET observations to systematically map the shift of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Shifts of vegetation phenology due to climate changes can affect vegetation productivity by affecting the process of carbon uptake [14][15][16][17]. Most of previous studies on vegetation phenology have demonstrated that the start of the growing season (SOS) and the end of the growing season (EOS) have, respectively, advanced and delayed trends under global warming [18][19][20]. Cheng et al [21] found that earlier SOS and later EOS led to an extension of the length of growing season (LOS) in the Tibetan Plateau, resulting in an increase of the gross primary productivity of vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Shifts of vegetation phenology due to climate changes can affect vegetation productivity by affecting the process of carbon uptake [14][15][16][17]. Most of previous studies on vegetation phenology have demonstrated that the start of the growing season (SOS) and the end of the growing season (EOS) have, respectively, advanced and delayed trends under global warming [18][19][20]. Cheng et al [21] found that earlier SOS and later EOS led to an extension of the length of growing season (LOS) in the Tibetan Plateau, resulting in an increase of the gross primary productivity of vegetation.…”
Section: Introductionmentioning
confidence: 99%